Cross-cultural adaptation and psychometric testing of the Quality of Dying and Death Questionnaire for the Spanish population. - Gutiérrez-Sánchez, Daniel; Cuesta-Vargas, Antonio (Elsevier, 2018)
Many measurements have been developed to assess the quality of death (QoD). Among these, the Quality of Dying and Death Questionnaire (QODD) is the most widely studied and best validated. Informal carers and health professionals who care for the patient during their last days of life can complete this assessment tool. The aim of the study is to carry out a cross-cultural adaptation and a psychometric analysis of the QODD for the Spanish population. The translation was performed using a double forward and backward method. An expert panel evaluated the content validity. The questionnaire was tested in a sample of 72 Spanish-speaking adult carers of deceased cancer patients. A psychometric analysis was performed to evaluate internal consistency, divergent criterion-related validity with the Mini-Suffering State Examination (MSSE) and concurrent criterion-related validity with the Palliative Outcome Scale (POS). The QODD-ESP-26 is a valid and reliable instrument for the assessment of the QoD of deceased cancer patients that can be used in a clinical and research setting.
Keywords: Cuidados paliativos; Muerte - Aspectos psicológicos; Cross-cultural adaptation; Psychometrics; Informal carers; Quality of dying and death; Palliative care; Outcome measure